Digitalización, interpretación y mediaciones en la exposición «Emilio Díaz. Esplendor del retrato fotográfico en Arequipa. 1893-1920», de 2018 - Zúñiga Bardales, Sergio Enrique (2024)
The digitization of heritage photographic archives is a recurring practice when doing research and exhibitions. These processes are of great importance since, through them, new material culture is created: new digital objects with particular characteristics that are different from the original. The digital objects arise from a technical process, which turns out to be the convergence of different subjectivities and points of view on the photographic object. The digitization is a mediated process by different humans the curator, conservator-restorer, digitizer and no-humans scanners, digital cameras. This contributes to the discussion of how a process that is often considered simply technical and almost objective is actually a performative cocreation between humans and non-humans whose decisions and agency restructure the meaning and value of the archive.